Pendampingan Ustaż dan Tuan Guru Pesantren Melalui Penguatan Nilai-nilai Multikultural Untuk Mencegah Radikalisme Islam Berbasis Pesantren di Kota Bima - Ruslan Ruslan; Luthfiyah Luthfiyah (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
Bima city has been called “Red Zone” area for radicalism dissemination. Prior reasearch indicated that the Islamic radicalism in Bima appeared from Islamic institution such as pesantren. This community service aimed at preventing Islamic radicalism in pesantren by sharing, educating and giving reinforcement of multicultural values to ustaż and Tuan Guru Pesantren (TGP). Community-Based Research (CBR) approach was employed because ustaż and TGP are the prior of pesantren’s community who can developed and transfer their understanding and religious perception to the students (santri). The results showed that ustaż and TGP had been more inclusive in their religion understanding, they transformed multicultural values to their student and all of pesantren’s community until this preventive step can prohibit the Islamic radicalism. They were also willing to involve the community service team in composing pesantren’s learning program. The team also give monthly visit for sharing idea about multicultural values.